Methods for mapping population distribution: An application to Obhur Municipality - Jeddah city - Alharbi, Alaa Mohamad (Journal of Humanities & Social Sciences, 2022)
This study aimed to reach the most effective method of cartographic representation that helps the researcher to prepare a map that fits his goals and objectives using geographic information systems, through the application on the Obhur municipality model in Jeddah and based on population statistics for the years 2004 and 2010 issued by the General Authority for Statistics, and the study included the production of maps Obhur municipality is the most widely used of both types of cartographic roads. Methods for representing absolute quantities (Circles method, Dot method) to represent population numbers and methods for representing interval quantities (Choropleth method) to represent population density and using the multiple representation method (Choropleth method and Proportional Circles method) to represent density and review the population distribution by gender and nationality, all maps were implemented on ArcMap 10.4 is an important GIS software. To achieve the goal, the descriptive analytical method and the cartographic method were adopted to compare the methods and know their methods, the most prominent advantages and disadvantages of them, and to analyze the maps. In this study, 11 different maps were prepared for the distribution of the population in the municipality of Obhur. Through it, it was concluded in this study, after comparing the implemented maps, that the Choropleth method using the quantitative intervals method is one of the best methods prepared and clear in representing the density according to the approved study data.
Keywords: cartographic representation; representation of absolute quantities; representation of interval quantities; relative circle map; point map; choropleth maps